PRIMATES SHOULD BE PROTECTED AND PUT UNDER CONSERVATION EFFORTS, NOT KEPT AS PETS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 21 April 2017 – Primates such as apes, monkeys, tarsiiformes (tarsiers) and lemuriformes (lemurs and slowloris) are endangered species, and will face extinction in the next few decades if urgent action is not taken to conserve them.